Identifikasi Bahaya, Penilaian Risiko dan Pengendalian Risiko dalam Kegiatan Bongkar Muat di PT Pelabuhan Indonesia IV cabang Makassar New Port - Pauline Aome; Kriswanto Widiawan (Jurnal Titra, 2022)
PT Pelabuhan Indonesia IV Makassar new port branch has a high potential danger. There will be 16 work accidents reported in 2020. The company has never identified a hazard in all of its business activities. Therefore the objective of the final task is to identify hazards, assess risks, control risk (HIRARC) in the company's main activities, namely loading and unloading activities. The initial stage of this final task is to conduct observations and interviews of workers directly in the company. After observation and interview, the study will identify hazards, assess risks, and control risks against risks that have high and extreme values. Hirarc's review on loading and unloading is expected to prevent similar accidents from happening again and reduce the impact of accidents. The results obtained after observation there were 10 activities with extreme category risk rating, 3 sub-activities with high category risk rating, and 9 sub-activities with medium category risk rating. After HIRARC the results obtained are 16 sub-activity risk rating medium category, 6 sub activity risk rating low category.